NUTRITIONAL HEALTH CHALLENGES AND LIFESTYLE PATTERNS AMONG NURSES IN THIRUVANANTHAPURAM, KERALA - MEERA D K (The Journal of Research ANGRAU, 2026)
This research conducted in 2019-20, aimed to assess the lifestyle patterns and nutritional status of nurses using a crosssectional, comparative approach with purposive sampling. The study included 500 registered female nurses, aged 25–45 years, from government and private hospitals in rural and urban regions of Thiruvananthapuram city. Findings revealed unhealthy lifestyle habits among nurses in both sectors, including insufficient physical activity (72% in government hospitals; 78% in private hospitals), inadequate sleep (51% and 56%, respectively), insufficient work breaks and difficulty in managing worklife balance. Underweight conditions were observed in 41% of government and 47% of private hospital nurses, together with poor dietary practices (40% and 70%, respectively). Biochemical analyses revealed high prevalence rates of anemia (50% in both sectors), diabetes (33% and 25%) and hypercholesterolemia (42% in both). These findings underscore critical gaps in nurses’ health and lifestyles, calling for urgent staff development initiatives and training programs by hospital authorities and policymakers to improve nurses’ well-being and care quality.